Phospholipase C and sphingomyelinase activities of the Clostridium perfringens α-toxin - Urbina, Patricia (2009)
Alfa-Toxin is a major pathogenic determinant of Clostridium perfringens, the causative agent of gas gangrene. Alfa-Toxin has been known for long to be a phospholipase C, but up to now its hydrolytic properties have been studied only through indirect methods, e.g. release of cell contents, or under non-physiological conditions, e.g., in micelles, or with soluble substrates. In this report we characterize the phospholipase C and sphingomyelinase activities of Alfa-toxin using a direct assay method (water-soluble phosphorous assay) with phospholipids in bilayer form (large unilamellar vesicles) in the absence of detergents. The simplest bilayer compositions allowing measurable activities under these conditions were DOPC:Chol (2:1 mol ratio) and SM:PE:Chol (2:1:1 mol ratio) for the PLC and SMase activities respectively. PLC activity was five times higher than SMase activity. Both activities gave rise to vesicle aggregation, after a lag time during which ca. 10% of the substrate was hydrolyzed. Vesicle aggregation, measured as an increase in light scattering, was a convenient semi-quantitative method for estimating the enzyme activities. The optimum pH for the combined PLC and SMase activities was in the 5–7 range, in agreement with the proposed role of -toxin in aiding the bacterium to escape the fagosome and survive within the cytosol.